Lead Concentration in Archaeological Animal Remains from The Edo Period, Japan: Is the Lead Concentration in Archaeological Goose Bone a Reliable Indicator of Domestic Birds?. (13th December 2013) - Eda, M.; Kodama, Y.; Ishimaru, E.; Yoneda, M.; Bejenaru, L.; Serjeantson, D.
ABSTRACT Lead pollution has increased over the past four centuries with industrialisation, urbanisation, and the use of motor vehicles. In Japan, lead concentrations in human bones of the Edo period (AD 1603–1867) from urban areas were found to be higher than those from suburban areas. Because most wild geese breed in the subarctic zone and winter in the temperate zone, it is to be expected that lead concentrations in archaeological goose bones from domestic individuals would be higher than those from wild individuals because of the difference in their life cycle. In this study, we measured and compared lead concentrations in bones of geese, other birds (duck, chicken, heron, and crow), mammals (dog, cat, pig/wild boar, and deer), and in a human tooth, all from the Kenmin‐kan Atochi site, Japan (Edo period). We found that lead pollution affected not only humans but also animals and that environmental lead pollution was widespread in the town. One of the goose bones analysed, a broken and healed ulna, showed a lead concentration approximately twice as high as the other goose bones. In addition, the lead concentration in a duck bone was much higher than in those of wild birds or mammals, which suggests that the duck had lived in an urban environment for a long time. The results suggest that analysis of lead concentrations can detect potential domestic animals that were exposed to environmental lead pollution, such as in the Roman period in Europe and in the Edo period in Japan. By accumulating comparative studies, the analysis of lead concentrations in archaeological goose bones is expected to become a reliable indicator of domestic geese under conditions of environmental lead contamination. Copyright © 2013 John Wiley & Sons, Ltd.